Designing strategies to tune reduction potential of organic molecules for sustainable high capacity battery application. Issue 9 (6th February 2017) - Araujo, Rafael B.; Banerjee, Amitava; Panigrahi, Puspamitra; Yang, Li; Strømme, Maria; Sjödin, Martin; Araujo, C. Moyses; Ahuja, Rajeev
Abstract : The framework of density functional theory has been applied to predict the formal potential of 137 molecules and identify promising candidates for the application as the organic electrode of rechargeable batteries. Abstract : Organic compounds evolve as a promising alternative to currently used inorganic materials in rechargeable batteries due to their low-cost, environmental friendliness and flexibility. One of the strategies to reach acceptable energy densities and to deal with the high solubility of known organic compounds is to combine small redox active molecules, acting as capacity carrying centres, with conducting polymers. Following this strategy, it is important to achieve redox matching between the chosen molecule and the polymer backbone. Here, a synergetic approach combining theory and experiment has been employed to investigate this strategy. The framework of the density functional theory connected with the reaction field method has been applied to predict the formal potential of 137 molecules and identify promising candidates for the referent application. The effects of including different ring types, e.g. fused rings or bonded rings, heteroatoms, and π bonds, as well as carboxyl groups on the formal potential, have been rationalized. Finally, we have identified a number of molecules with acceptable theoretical capacities that show redox matching with thiophene-based conducting polymers which, hence, are suggested as pendent groups for the development of conducting redox polymer based electrode materials.